Preventive Maintenance Interval Prediction: a Spare Parts Inventory Cost and Lost Earning Based Model - Adebimpe, O. A.; Oladokun, V.; Charles-Owaba, O. E. (Engineering, Technology & Applied Science Research, 2015)
In this paper, some preventive maintenance parameters in manufacturing firms were identified and used to develop cost based functions in terms of machine preventive maintenance. The proposed cost based model considers system’s reliability, cost of keeping spare parts inventory and lost earnings in deriving optimal maintenance interval. A case of a manufacturing firm in Nigeria was observed and the data was used to evaluate the model.